Mitochondrial DNA haplogroups and type 2 diabetes: a study of 897 cases and 1010 controls. - Chinnery, P; Mowbray, C; Patel, S; Elson, J; Sampson, M; Hitman, G; McCarthy, M; Hattersley, A; Walker, M (2007)
Mitochondria play a central role in the secretion of insulin by pancreatic beta-cells, and pathogenic mutations of mitochondrial DNA (mtDNA) can cause diabetes. The aetiology of type 2 diabetes has a strong genetic component, raising the possibility that genetic variants of mtDNA alter the risk of developing the disorder. Recent studies have produced conflicting results. By studying 897 UK cases of type 2 diabetes and 1010 population-matched controls, it is shown that European mtDNA haplogroups are unlikely to play a major role in the risk of developing the disorder.